Analysis of Climate Change and Extreme Climatic Events in the Lake Victoria Region of Tanzania - Luhunga, Philbert Modest; Songoro, Alexander Elias (Frontiers in Climate, 2020)
An analysis of climate change and the associated climate extreme events at regional and local scales is an important stage for planning and developing feasible adaptation and mitigation strategies and policies for reducing the impacts of climate change. In this paper, we present an analysis of climate change and the associated extreme climate events in the Lake Victoria region of Tanzania focusing on Kagera and Geita regions. We use daily simulated climate variables (rainfall, minimum and maximum temperatures) from the Coordinated Regional Climate Downscaling Experiment Program Regional Climate Models (CORDEX_RCMs) for the analysis. Extreme climate indices, rainfall, minimum and maximum temperatures time series during historical (1971-2000) climate are compared with future (2011-2100) climate condition under two Representation Concentration Pathways (RCP): RCP 4.5 and RCP 8.5 emission scenarios. Statistical analysis such as the Mann-Kendall (MK) non-parametric test and Theil-SEN slope estimator is used to estimate the existence, magnitude, and statistical significance of potential trends in climate data time series. Results show that during historical (1971-2000) climate condition the Lake Victoria region of Tanzania experienced a statistically significant increasing trend in temperature and a non-significant decreasing trend in rainfall. These have contributed to a statistically significant increase in extreme climate events that related to frequency, intensity and duration of rainfall, and temperature. In future climate condition (2011-2100), the Lake Victoria region is likely to experience increased temperatures and rainfall under both RCP 4.5 and RCP 8.5 emission scenarios. This will contribute to a significant increasing trend in extreme climatic events such as heavy rainfall and extremely heavy rainfall. The frequency of cold events (cold days, and cold nights) is likely to decrease while the frequency of warm events (warm days and warm nights) are likely to increase significantly. These results indicate that in the future climate, both Kagera and Geita regions are likely to experience significant damage to properties, destruction of infrastructures, and other socio-economic livelihoods of people from climate-related stresses. It is therefore recommended that appropriate planning and effective adaptation policies should be put in place for disaster risk prevention